When did the ultrahigh-pressure rocks reach the surface?: a@207Pb/206Pb zircon, 40Ar/39Ar white mica, Si-in-white mica, single-grain provenance study of Dabie Shan synorogenic foreland sediments - Grimmer, Jens Carsten; Ratschbacher, Lothar; McWilliams, Michael; Franz, Leander; Gaitzsch, Ines; Tichomirowa, Marion; Hacker, Bradley R.; Zhang, Yueqiao (Chemical geology, 2003)
A single-grain study of synorogenic, Triassic-Jurassic quartz arenites of the eastern and southern forelands of the ultrahigh-pressure (UHP) Hong'an-Dabie orogen illustrates the utility and sensitivity of three provenance analysis techniques. 40Ar/39Ar detrital white mica ages indicate that the Middle Triassic stratigraphic level reached ∼400 °C at ∼125 Ma, probably heated by latest Jurassic-Early Cretaceous intrusions. Un-reheated single grains are as young as the depositional age of their sedimentary hosts and yield a Triassic-Jurassic age maximum that indicates a Hong'an-Dabie source, and some Paleozoic and Proterozoic ages that are mostly younger than 207Pb/206Pb detrital zircon ages. Si contents of detrital white micas from the same samples range from 3.0 to 3.6 atoms pfu, with ∼70% of the micas having <3.3 Si atoms pfu. The grains with 3.3-3.6 Si atoms pfu probably originated from Hong'an-Dabie, indicating initial exposure of high-pressure (HP) and even ultrahigh-pressure rocks during the Middle Jurassic. The single-grain evaporation 207Pb/206Pb ages of detrital zircons provide little indication that one of Earth's most spectacular unroofing processes was active in the adjacent orogen. Proterozoic and Silurian zircon ages abound, indicating that the detritus originated from the northern margin of the Yangtze craton and regions to the southeast, in particular the South China fold belt and the Cathaysia block, but only a few Triassic zircon ages, indicating a Hong'an-Dabie source, were measured. The Triassic signal is smallest because growth of metamorphic zircon is rare and is mostly limited to rim formation on pre-existing zircons, and because neither a magmatic arc nor syn- to post-collisional magmatism have been mapped in the Hong'an-Dabie orogen. Based on the white mica ages and the Si-in-white mica analysis, the Hong'an-Dabie orogen provided as much as 80% of the foreland detritus. The ages of the oldest micas suggest that exhumation of Hong'an-Dabie began at 240±5 Ma and thus the average exhumation rates exceeded 2 mm/year during the Middle Triassic to Middle Jurassic.
Im Titel sind die Ziffern "207", " 206", "40" und "39" hochgestellt
Gesehen am 23.09.2020